Evaluasi Kinerja Mengajar Guru IPS Dalam Mengimplementasikan TPACK - Joni Ruta Pulungtana; Yari Dwikurnaningsih (Universitas Pendidikan Ganesha, 2020)
The purpose of this study was to evaluate the teaching performance of social studies teachers in implementing TPACK, from the aspects of planning, implementation, and evaluation of learning in Satya Wacana Christian High School. This type of research is an evaluative study, with research subjects Teachers who are members of the Social Sciences specialization group with a total of 7 teachers. Data collection techniques using observation, study documents, questionnaires, and interviews. Qualitative data analysis techniques are performed by data collection, data reduction, data presentation, and conclusions. The quantitative data are analyzed in a simple descriptive manner by calculating the mean, percentage and categorized. The results of this research are from aspect of lesson planning, overall are in the good category with a percentage of 84.66%. From the aspect of the implementation of learning overall is in the good category with a percentage of 81.25%. From the aspect of learning evaluation overall is in the good category with a percentage of 85.78%.